Research Concerning the Bending Properties of Reconstituted Spruce Lumber Boards, Obtained by Edge-Cutting at 45° and Gluing - Porojan, Mihaela; Brandstetter, Markus; Ispas, Mihai; Bedelean, Bogdan; Campean, Mihaela (MDPI AG, 2021)
The best-possible valorization of each cut log is a priority. The aim of this research was to evaluate the potential of a solution for increasing the conversion efficiency of tapered logs, by edge-cutting the narrowest sideboards at 45 and joining them by gluing, in order to obtain usable lumber boards. The modality of obtaining the glued elements was described and the values of the density and bending properties (MOE and MOR) of these elements compared to solid wood elements taken from the same logs and the same position within each log was determined. The envisaged outcome was to determine if the bonded products are suited to be used as cores within laminated products for construction.
Keywords: spruce wood; reconstituted lumber